6X-43=3X-22

Simple and best practice solution for 6X-43=3X-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6X-43=3X-22 equation:


Simplifying
6X + -43 = 3X + -22

Reorder the terms:
-43 + 6X = 3X + -22

Reorder the terms:
-43 + 6X = -22 + 3X

Solving
-43 + 6X = -22 + 3X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-3X' to each side of the equation.
-43 + 6X + -3X = -22 + 3X + -3X

Combine like terms: 6X + -3X = 3X
-43 + 3X = -22 + 3X + -3X

Combine like terms: 3X + -3X = 0
-43 + 3X = -22 + 0
-43 + 3X = -22

Add '43' to each side of the equation.
-43 + 43 + 3X = -22 + 43

Combine like terms: -43 + 43 = 0
0 + 3X = -22 + 43
3X = -22 + 43

Combine like terms: -22 + 43 = 21
3X = 21

Divide each side by '3'.
X = 7

Simplifying
X = 7

See similar equations:

| 12X+134=6X+80 | | 3ln(x)+8=ln(3x)+12 | | 4psquared-12p+7=0 | | 45logx=3 | | 10X+36=6X+20 | | 34-9k=88 | | -5X-40=-3X-26 | | 2x^2-25x+80=0 | | -(3w+4)+5(w-2)-3(6w-8)=1 | | (x+35)=(3x+5) | | 10x^2+9x-117=0 | | 3x+8=4x-10 | | 10x^2+9x-108=0 | | -2x^2+54x=0 | | 6(y-6)/10(y-6) | | H(5x)=3x^2+2 | | 2x^2+52x=0 | | 25x+16y=287.28 | | 2x^2+18x+162=0 | | -2(2x-4x)=6+18 | | 4=2k+22 | | (9y^2-8y+8)-(3y^2-8y+2)= | | -8b+3+6b=3b+8 | | x*1.618=60 | | 5y-8=-28 | | Y^2+18y+69=0 | | 28+9=2n | | 4x/5x-10=35 | | (3.99)2x+19.99y=111.88 | | 2r+12=6 | | -16t^2+25t+10= | | (4x^3-6x+7)=(-19x^3-15x-18) |

Equations solver categories